(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The aim of this work is to automate the conventional power hacksaw machine in order to achieve high productivity of work-pieces than the power hacksaw machine using pneumatic power. Pneumatic is a huge topic of engineering dealing with the mechanical properties of air. In our project we take this pneumatic and a hacksaw for cutting purpose, The pneumatic high-speed hacksaw machine has an advantage of working in high air pressure , the hacksaw used in this is reciprocate such that required shape can be cut according to the requirement. The hacksaw is the metal cutting machine tool designed to cut metal by applying air pressure. Hacksaws are used to cut thin and soft metals the operation of the unit is simplified to a few simple operations involving a cylinder bore and piston arrangement. There are numerous systems in hacksaw machine.